Measuring Changes of Students’ Statistical Reasoning Taught by Ethnomathematics Approach Assisted TinkerPlots: A Stacking Analysis Study - Ramadhani, Rahmi; Saragih, Sahat; Maulida, Rizki; Simanjuntak, Sinta Makito Br (Universitas Muhammadiyah Mataram, 2022)
This study aims to use the Rasch model stacking analysis technique to assess students' statistical reasoning abilities in descriptive statistics learning utilizing a TinkerPlots-assisted ethnomathematics approach in Nias cultural environment. This research is a quasi-experimental study that uses pre-and post-test control group designs. The stacking technique is used to examine how students' statistical reasoning abilities change in the presence of the intervention. The sample for this study is students in the 12th year at Gunungsitoli High School in the Nias Islands, Sumatera Utara region. Students are administered an exam that consists of five essay questions. Their responses are evaluated using a rubric that incorporates diagnostic criteria and a response certainty index. The data is analyzed using the Rasch Partial Credit Model with WINTSTEPS 4.5.5. The results indicate that students in the experimental group improved their statistical reasoning abilities more than students in the control group when they used TinkerPlots-assisted ethnomathematics in Nias cultural environment (the group with an ordinary learning approach). Along with the intervention, it is discovered that changes in student learning capacities are achievable in some situations due to pupils receiving the correct response or cheating. In other circumstances, pupils who undergo negative changes may respond inappropriately due to carelessness, boredom, or misconceptions. Additionally, these findings demonstrate that some children provide correct responses following intervention on certain items. According to the findings of this study, stacking analysis approaches are critical for describing each change in student abilities as a result of each person and each item.